Analisis Pengaruh Engine Temperature Terhadap Laju Konsumsi Bahan Bakar Mobil Hemat Energi Kategori Urban Etanol - Muhammad Bagus Laroybafih; Samsudin Anis; Miftakhun Nuril; Fitroh Miftahul Huda; Akhlis Rahman Sari Nurhidayat; Nur Akhlis Sarihidaya Laksana (P3M Politeknik Negeri Cilacap, 2026)
A crucial global issue is the world's dependence on fossil fuels as its primary energy source. An alternative solution to this problem is to use fuels such as ethanol. Using ethanol as fuel requires comprehensive optimization of the vehicle system, including the engine's temperature control. This research aims to determine the effect of engine operating temperature variations on fuel efficiency thru 4 engine temperature variations: 70, 80, 90, and 100 degrees Celsius, using two approaches: static and dynamic. The test results show that engine temperature affects fuel consumption and engine operating stability. Based on the experiments conducted, it was concluded that a temperature of 90°C is the most optimal working temperature, with an increase of 9.91% in static testing and 14.74% in dynamic testing (compared to the temperature with the lowest efficiency). It can be concluded that 90°C is recommended as the optimal working temperature for ethanol engines in the development of energy-efficient vehicles.